A orientação espacial na pré-escola: analisando saberes docentes - Cavalcante, Cristiane de Oliveira (2015)
According to Brazilian official documents, the area of school mathematics is divided into four blocks or axes: Numbers and Operations, Space and Shape (Geometry), Quantities and Measurements, and Treatment Information (Statistics). The teaching of mathematics, however, is still very focused on the first, at the expense of other blocks. Two decades ago, several researchers (PAVANELLO, 1993; ARAÚJO, 1994; LORENZATO, 1995; FAINGUELERNT, 1995) denounced the abandonment of geometry, which includes content related to form and space, in Basic Education and defended their appreciation. In the past decade, legal provisions determined the inclusion of Pre-School in compulsory basic education. With regard to the pedagogical work with the geometry at this stage of early childhood education, often the educator addresses only the (re) knowledge of plane geometric figures - circle, triangle, rectangle, square - in painting and appointment activities. Teaching and Geometry learning, however, need to create opportunities, as proposed by several researchers - (GRANDE, 1994) (CERQUETTI-ABERKNE; BERDONNEAU, 1997) (DUHALDE; Cuberes, 1998) (Smole; DINIZ; CANDID , 2003), (Lorenzato, 2006) - the development of concepts for space and form, giving children opportunities to realize and know the areas in which they live, they move, where they learn to explore, conquer, order and represent. This study aimed to identify the teachers´s knowledge of teachers who teach the spatial orientation on Pre-School. The qualitative research, case study type, was carried out in an institution of Early Childhood Education and Elementary Education municipal fortress system. Study participants were two teachers, one of child IV and of child V, and a trainer of early childhood education. Over nine meetings were held periodic visits to the realization of field observations of classes taught by teachers participating research and interviews (initial and reflective), which were recorded and later transcribed, generating texts and reflections. From the results, it was found that, despite having some geometry knowledge, the teacher´s knowledge of teachers and trainer regarding the spatial orientation, an important content in the development and learning of children from pre-school, are fragmented, requiring provide urgently training opportunities that enhance and articulate such knowledge.